Three dimensional modeling and numerical analysis of hydrogen effects on the thermomechanical response of Nickel–Titanium orthodontic applications. (1st December 2022) - Ulff, N.; Bouby, C.; Zineb, T. Ben
Abstract: This paper deals with effects of the hydrogen presence on the thermo-mechanical behavior of NiTi shape memory alloys (SMAs), widely considered for manufacturing orthodontic archwires. A three dimensional phenomenological model is formulated, based on thermodynamics of irreversible processes. It takes into account the experimentally observed effects on the main physical mechanisms (martensitic transformation and reorientation of martensite). The assumption of an additive decomposition between a reversible lattice and a trapped hydrogen concentrations is adopted. The complete problem including chemical, thermal and mechanical balanced equations and their weak form are solved by the finite element method. A 3D hexahedral continuum finite element with five degrees of freedom per node (displacements, temperature and total hydrogen concentration) is developed. Its implementation is carried out in the Abaqus finite element software. Numerical results are presented and compared to experimental ones which show the significant effects of the hydrogen presence in NiTi SMA. Highlights: Effects of the hydrogen presence on the thermo-mechanical behavior of NiTi shape memory alloys (SMAs) A 3D phenomenological model, based on thermodynamics of irreversible processes Additive decomposition between a reversible lattice and a trapped hydrogen concentrations. Finite element method to solve the complete coupled problem. Development of a 3D hexahedral continuum finite element with 5 degrees of freedom per node (u, T and hydrogen concentration). A significant effect of the hydrogen on NiTi SMA from numerical and experimental results